«Fragile»: un nuovo immaginario del progresso - Cucci, Giovanni ca. 20./21. Jh. (La civiltà cattolica, 2021)
Francesco Monico’s book Fragile. Un nuovo immaginario del progresso [Fragile. A New Image of Progress] investigates the idea of progress as it has been elaborated during the modern era. Resuming the conception of man as Homo fictus, built by imagination, the author states that it is precisely to imagination that we owe the idea of progress. The forgetfulness of this «fantastic» origin has led modernity to disregard some fundamental aspects of reality, with serious consequences on a cultural, economic, political and environmental level. If it is to the imagination that we owe the «fragile» notion of progress, the way out can be identified by some equally present counter-images, even if these are less pronounced. In Monico’s book, three of these are mentioned: the importance of degrowth (Latouche), the heterogeny of ends (Vico), a good life, which is concretely implemented in a community (the Amish).